2018
DOI: 10.1111/jen.12584
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and sampling plan of the phytophagous stink bug complex in different soybean production systems

Abstract: Phytophagous stink bugs are major soybean pests, and knowledge of spatial distribution models of the pest in the crop is fundamental to establishing an appropriate sequential sampling plan, and thus, allowing the correct utilization of control strategies. This work aimed to study the spatial distribution of phytophagous stink bugs in soybean grown in different cropping systems and determine a sequential sampling plan. The experiment was conducted in Maracaju, MS, Brazil, during the agricultural year of 2012/20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
1
9
0
1
Order By: Relevance
“…On the other hand, according to the same authors, a movement of E. heros adults toward an aggregate distribution was observed based on the k index throughout its occurrence in cotton, corroborating this study on E. meditabunda. Fernandes et al, (2018) reported similar results for adults and the total population (nymphs + adults) of phytophagous stink bugs in soybean, where a strong aggregation of these insects was observed, regardless of the variety and system of soybean production. Also, based on the k index, the distribution of nymphs was aggregate in most evaluations.…”
Section: Dispersion Indicessupporting
confidence: 55%
See 3 more Smart Citations
“…On the other hand, according to the same authors, a movement of E. heros adults toward an aggregate distribution was observed based on the k index throughout its occurrence in cotton, corroborating this study on E. meditabunda. Fernandes et al, (2018) reported similar results for adults and the total population (nymphs + adults) of phytophagous stink bugs in soybean, where a strong aggregation of these insects was observed, regardless of the variety and system of soybean production. Also, based on the k index, the distribution of nymphs was aggregate in most evaluations.…”
Section: Dispersion Indicessupporting
confidence: 55%
“…The aggregation indices used to verify the degree of aggregation of the E. meditabunda were: variance/mean ratio and the Morisita and K indexes (Fernandes et al, 2018), while the theoretical frequency distributions used do evaluate the spatial distribution were: Poisson and negative binomial distributions, according to the methodology reported by Fonseca et al (2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Outbreaks of the main soybean pests occur in nonuniform spatial distributions [20]. The spatial distribution is characterized as aggregating for species of the complex of defoliating caterpillars [37,38] and stink bugs [39,40]. In addition, pest inspection using beat-cloth is still currently being used as a traditional sampling method in soybean crops.…”
Section: Discussionmentioning
confidence: 99%